2021
DOI: 10.1111/myc.13351
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of rhino‐orbital mucormycosis in an educational therapeutic hospital during the COVID‐19 pandemic in western Iran: An observational study

Abstract: Background: COVID-19 patients, especially the patients requiring hospitalisation, have a high risk of several complications such as opportunistic bacterial and fungal infections. Mucormycosis is a rare and opportunistic fungal infection that mainly affects diabetic and immunocompromised patients. An increase has been observed in the number of rhino-orbital mucormycosis in patients with COVID-19 admitted to Imam Khomeini Hospital, Kermanshah, Iran, since October 2020. This is a report of the frequency, risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…[ 37 ] India Prospective Single-center 80 May 2021–Aug 2021 69 (55) 90 (72) Ismaiel WF. [ 38 ] Egypt Retrospective Single-center 10 Avatef Fazeli M. [ 39 ] Iran Retrospective Single-center 9 Oct 2020–Nov 2020 59 33 (3) 78 (7) Goddanti N. [ 40 ] India Retrospective Single-center 300 Apr 2021–Jun 2021 49 ± 12 74 (222) 96 (287) Kulkarni R. [ 41 ] India Retrospective Multi-center 49 Dec 2020–Jun 2021 53 ± 11 71 (35) 82 (40) Dokania V. [ 42 ] India Prospective Single-center 21 Apr 2021–Jun 2021 50 ± 14 71 (15) 90 (19) Nair AG. [ 43 ] India Retrospective Multi-ce...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ] India Prospective Single-center 80 May 2021–Aug 2021 69 (55) 90 (72) Ismaiel WF. [ 38 ] Egypt Retrospective Single-center 10 Avatef Fazeli M. [ 39 ] Iran Retrospective Single-center 9 Oct 2020–Nov 2020 59 33 (3) 78 (7) Goddanti N. [ 40 ] India Retrospective Single-center 300 Apr 2021–Jun 2021 49 ± 12 74 (222) 96 (287) Kulkarni R. [ 41 ] India Retrospective Multi-center 49 Dec 2020–Jun 2021 53 ± 11 71 (35) 82 (40) Dokania V. [ 42 ] India Prospective Single-center 21 Apr 2021–Jun 2021 50 ± 14 71 (15) 90 (19) Nair AG. [ 43 ] India Retrospective Multi-ce...…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ] 75 (60) 1.3 (1) Ismaiel WF. [ 38 ] Avatef Fazeli M. [ 39 ] 44 (4) 22 (2) 11 (1) 13 (1) 100 (7) 25 (2) Goddanti N. [ 40 ] 60 (180) 79 (237) Kulkarni R. [ 41 ] 37 (18) Dokania V. [ 42 ] 0.5 (1) 4.8 (1) 90 (19) 19 (4) Nair AG. [ 43 ] 38 (5) 54 (7) …”
Section: Resultsmentioning
confidence: 99%
“…Reports of CAM outside the Indian population are scarce, 25 most of which are case reports. 28 In Iran, two cross-sectional studies from Tehran 20 and west Iran 29 have reported on 15 and 12 CAM cases, of which 86% and 87.3% had DM, with a mortality rate of 47% and 66.6%, respectively. A series of 10 cases with CAM were also reported from Pakistan, 30 of which 70% were diabetic and 80% had received corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Many other countries have also reported a sudden surge in cases of CAM during the past few months, suggesting that this condition could soon emerge as a global problem. 11 Even before the pandemic, mucormycosis has been known to occur in patients with immunodeficiency, mainly in those with uncontrolled diabetes and ketoacidosis. 12,13 In the largest study on CAM to date, Sen et al 4 clearly showed that uncontrolled diabetes and use of high-dose systemic corticosteroids were the main risk factors for CAM.…”
mentioning
confidence: 99%